Development of pocketbook based on higher order thinking skills of heat and transfer material for fifth grade students - Elvia Silviana Lase; Neni Hermita; Gustimal Witri (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2022)
This study aims to assist students in understanding learning materials in science subjects by developing a pocketbook. A pocketbook is a small book that can be stored in a pocket and easy to carry everywhere. This practicality can help students to gain knowledge anywhere and anytime by using a pocketbook. So, the need for innovation and habituation, the researchers develop practical teaching materials that students can learn anywhere and adapting to the demands of the times, namely pocketbook based on high order thinking skills (HOTS) of heat and transfer materials for fifth graders of elementary school. It is expected that students will be able to develop creative thinking skills, high-level thinking and be able to solve problems in their daily lives by using students' thinking skills. The display of colorful pocketbooks, lots of pictures, unique layouts, and clear language makes students have new learning experiences without losing the essence/meaning of the material. The development model used is ADDIE (Analysis, Design, Development, Implementation and Evaluation). Data collection techniques, using product validation questionnaires by educational technology, material experts, and linguist experts, teacher response questionnaires and student response questionnaires. The results obtained from the development of HOTS-based pocketbook teaching materials are very valid. Besides, the teacher and students have positive response toward the developed pocketbook. This research is expected to help teachers in developing students' high-level and creative thinking skills, as well as being a reference in developing HOTS-based pocketbooks in the future.